Back-to-back volleyball tournaments for UiTM ladies' players - Sim, Sandra Phek Lin (UiTM Sarawak, 2021)
With support and motivation from Professor Dato Dr. Jamil bin Hj. Hamali (Rector of UiTM Sarawak) and Dr. Kamarudin bin Jaraee (President of KEKITA Sarawak Branch). UiTM ladies volleyball players participated in two back-to-back volleyball tournaments in August 2019. In conjunction with Kuching August Festival 2019, the UiTM ladies’ volleyball team, comprising 9 players took part in ‘Kejohanan Bola Tampar Wanita Piala Datuk Bandar MBKS Kali-1.2019" held from Ist August to4August 2019 at Indoor Stadium MBKS. Associate Professor Dr. Sandra Sim Phek Lin was the Team manager cum Captain, and the players were Zainon Binti Bibi. Asfalaila Binti Ibrahim. Napsiah Binti Putit. Nurul Huda, Aima Sumiyati Binti Maliki. Suhaida Binti Halamy, Cecilia Ak Nerok and Nuruliana Khazhila Binti Edris.